2016
DOI: 10.3390/metabo6040034
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Mammalian Cell Proliferation and Macromolecule Synthesis Using Deuterated Water and Gas Chromatography-Mass Spectrometry

Abstract: Deuterated water (2H2O), a stable isotopic tracer, provides a convenient and reliable way to label multiple cellular biomass components (macromolecules), thus permitting the calculation of their synthesis rates. Here, we have combined 2H2O labelling, GC-MS analysis and a novel cell fractionation method to extract multiple biomass components (DNA, protein and lipids) from the one biological sample, thus permitting the simultaneous measurement of DNA (cell proliferation), protein and lipid synthesis rates. We ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 59 publications
1
32
0
Order By: Relevance
“…The DNA pellet was left to dry for 15 min, then resuspended in H 2 O (200 μL) and was incubated at 55 °C for 10 min followed by vortex mixing. The resuspended DNA samples were hydrolyzed and dephosphorylated by the addition of S1 nuclease and potato acid phosphatase as previously described [17]. After hydrolysis, the deoxyribose moiety was derivatized in a two-step reaction as we have previously detailed [17].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DNA pellet was left to dry for 15 min, then resuspended in H 2 O (200 μL) and was incubated at 55 °C for 10 min followed by vortex mixing. The resuspended DNA samples were hydrolyzed and dephosphorylated by the addition of S1 nuclease and potato acid phosphatase as previously described [17]. After hydrolysis, the deoxyribose moiety was derivatized in a two-step reaction as we have previously detailed [17].…”
Section: Methodsmentioning
confidence: 99%
“…The resuspended DNA samples were hydrolyzed and dephosphorylated by the addition of S1 nuclease and potato acid phosphatase as previously described [17]. After hydrolysis, the deoxyribose moiety was derivatized in a two-step reaction as we have previously detailed [17]. The perfluorotriacetyl derivative of DNA-bound deoxyribose was analyzed by GC–MS in the negative chemical ionization (NCI) mode (Agilent 7890B GC system and an Agilent 5977B MSD) with helium as the carrier and methane as the reagent gas.…”
Section: Methodsmentioning
confidence: 99%
“…Hexane and aqueous layers were dried at 50°C and 70°C, respectively, under N 2 gas. Selected ion monitoring (SIM) was performed a 159m/z (M 0 ) to 164m/z to obtain the peak areas of both derivatized glycerol triacetate ion and d 5 -glycerol triacetate ion, respectively (Foletta et al, 2016). Glycerol in the samples was quantified using an unlabeled glycerol standard series normalized to the internal standard (d 5 -glycerol).…”
Section: Hydrolysis Of Lipid Fractionsmentioning
confidence: 99%
“…By adding D2O to the drinking water of mice, previous studies showed the incorporation of deuterium into the total biomass in various mouse organs but could not image and differentiate D-labeled lipids and proteins in situ [5][6][7][8] . Using DO-SRS imaging with macromolecular selectivity, we found that different mouse organs show metabolic preference to either protein or lipid biosynthesis, which reflects their different functions (Supplementary Figure 4A).…”
Section: Visualizing De Novo Lipogenesis and Metabolic Homeostasis Inmentioning
confidence: 99%
“…By applying DO-SRS to living cells and animals, we not only demonstrated its broad utility, high sensitivity, noninvasiveness, subcellular resolution, compatibility with other imaging modality, and suitability for in vivo live imaging in mammals, but also gained new insights on the metabolic basis of several biological processes. respectively [6][7][8] (Figure 1A). As often the rate-limiting step, the synthesis of C-D bondcontaining macromolecules from the precursors is governed by cellular metabolic activities.…”
Section: Introductionmentioning
confidence: 99%